2020
DOI: 10.1016/j.bbih.2020.100077
|View full text |Cite
|
Sign up to set email alerts
|

Chronic HIV-1 Tat exposure alters anterior cingulate cortico-basal ganglia-thalamocortical synaptic circuitry, associated behavioral control, and immune regulation in male mice

Abstract: HIV-1 selectively disrupts neuronal integrity within specific brain regions, reflecting differences in viral tropism and/or the regional differences in the vulnerability of distinct neuronal subpopulations within the CNS. Deficits in prefrontal cortex (PFC)-mediated executive function and the resultant loss of behavioral control are a particularly debilitating consequence of neuroHIV. To explore how HIV-1 disrupts executive function, we investigated the effects of 48 h, 2 and/or 8 weeks of HIV-1 Tat exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 160 publications
(251 reference statements)
3
47
3
Order By: Relevance
“…These data were in contrast to previous literature that found distinct memory and cognitive impairments (36,43,58,59). It is possible that differences observed in behavioral trends in this study compared to previous reports could be attributed to different readouts in a test, such as MWM conducted over 4 days in this study vs. 18 days in a previous study (43), or due to differences in two strains of Tat mice, which differ in Tat copy number (42). Additionally, two induction paradigms present different handling requirements and it is not known if additional handling of mice during injection may change their response to behavior.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These data were in contrast to previous literature that found distinct memory and cognitive impairments (36,43,58,59). It is possible that differences observed in behavioral trends in this study compared to previous reports could be attributed to different readouts in a test, such as MWM conducted over 4 days in this study vs. 18 days in a previous study (43), or due to differences in two strains of Tat mice, which differ in Tat copy number (42). Additionally, two induction paradigms present different handling requirements and it is not known if additional handling of mice during injection may change their response to behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…HIV-1 proteins including Tat and glycoprotein120 (gp120) are implicated in direct or indirect mechanisms that manifest into anxiety-like symptoms ( 52 ). Indeed, several previous reports investigated Tat-induced anxiety and/or stress, including sex-specific differences, in transgenic HIV-1 Tat rodent models ( 42 , 43 , 48 , 53 ). Since our investigations did not focus on sex-specific changes, we did not test for sex as a confounding variable for anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the proinflammatory effects of HIV-1 Tat at C-C chemokine receptor type 5 (CCR5) desensitize MOR or δ-opioid receptors (DOR [ 51 53 ]), an effect that appears to contribute to decreased antinociceptive potency of morphine in Tat transgenic mice [ 54 ]. Interestingly, recent research has demonstrated long-term immune tolerance to repeated inflammatory insult within resident microglia in the CNS, which could impact the response to morphine after chronic Tat exposure [ 55 58 ].…”
Section: Introductionmentioning
confidence: 99%